L-leucine increases the sensitivity of drug-resistant Salmonella to sarafloxacin by stimulating central carbon metabolism and increasing intracellular reactive oxygen species level - Yang, Heng; Zhou, Yanhong; Luo, Qiong; Zhu, Chunyang; Fang, Binghu (Frontiers in Microbiology, 2023)
The overuse of antibiotics has made public health and safety face a serious crisis. It is urgent to develop new clinical treatment methods to combat drug-resistant bacteria to alleviate the health crisis. The efficiency of antibiotics is closely related to the metabolic state of bacteria. However, studies on fluoroquinolone-resistant Salmonella are relatively rare. In this study, non-targeted metabonomics was used to analyze the metabolic difference between sarafloxacin-sensitive Salmonella typhimurium(SAR-S) and sarafloxacin-resistence Salmonella typhimurium(SAR-R), and found that the central carbon metabolism was weakened due to drug resistance. We also confirmed that exogenous L-leucine increased the killing effect of sarafloxacin on SAR-R and other clinically resistant Salmonella serotypes. Exogenous L-leucine stimulated the metabolic state of bacteria, especially the TCA cycle, which increased the working efficiency of the electron transfer chain and increased the intracellular NADH, ATP concentration , and reactive oxygen species level. Furthermore, we used Quantitative Real time PCR to confirm the changes in various metabolic characteristics. Our results suggest that when the metabolism of drug-resistant bacteria is reprogrammed, the bactericidal effect of antibiotics improves. This study further enhances research in the anti-drug resistance field at the metabolic level and provides theoretical support for solving the current problem of sarafloxacin drug resistance, a unique fluoroquinolone drug for animals. To sum up, our research results showed that exogenous L-leucine promotes the bactericidal effect of antibiotics through metabolic modification of drug-resistant bacteria, which has the potential as a new adjuvant of antibiotics.